Sesamol-Loaded PLGA Nanosuspension for Accelerating Wound Healing in Diabetic Foot Ulcer in Rats - Gourishetti K (Dove Medical Press, 2020)
Karthik Gourishetti,1 Raghuvir Keni,1 Pawan Ganesh Nayak,1 Srinivas Reddy Jitta,2 Navya Ajitkumar Bhaskaran,2 Lalit Kumar,2 Nitesh Kumar,1 Nandakumar Krishnadas,1 Rekha Raghuveer Shenoy1 1Department of Pharmacology, Manipal College of Pharmaceutical Sciences, Manipal Academy of Higher Education, Manipal 576104, Karnataka, India; 2Department of Pharmaceutics, Manipal College of Pharmaceutical Sciences, Manipal Academy of Higher Education, Manipal 576104, Karnataka, IndiaCorrespondence: Rekha Raghuveer ShenoyDepartment of Pharmacology, Manipal College of Pharmaceutical Sciences, Manipal Academy of Higher Education, Manipal 576104, Karnataka, IndiaTel +91-820-2922482Fax +91-820-2571998Email rekhaarunt@gmail.comBackground: Diabetic foot ulcer is an intractable complication of diabetes, characterized by the disturbed inflammatory and proliferative phases of wound healing. Sesamol, a phenolic compound, has been known for its powerful antioxidant, anti-inflammatory, anti-hyperglycaemic and wound healing properties. The aim of the present study was to develop a sesamol nano formulation and to study its effect on the various phases of the wound healing process in diabetic foot condition.Methods: Sesamol-PLGA (SM-PLGA) nanosuspension was developed  using nanoprecipitation method. TEM, in vitro drug release assay and in vivo pharmacokinetic studies were performed for the optimised formulation. Diabetic foot ulcer (DFU) in high fat diet (HFD)-fed streptozotocin-induced type-II diabetic animal model was used to assess the SM-PLGA nanosuspension efficacy. SM-PLGA nanosuspension was administered by oral route. TNF-α levels were estimated using ELISA and Western blot analysis was performed to assess the effect on the expression of HSP-27, ERK, PDGF-B and VEGF in wound tissue. Wound re-epithelization, fibroblast migration, collagen deposition and inflammatory cell infiltration were assessed by H&E and Masson’s trichrome staining. Effect on angiogenesis was assessed by CD-31 IHC staining in wound sections.Results: The optimized SM-PLGA nanosuspension had an average particle size of < 300 nm, PDI< 0.200 with spherical shaped particles. Approximately 80% of the drug was released over a period of 60 h in in vitro assay. Half-life of the formulation was found to be 13.947 ± 0.596 h. SM-PLGA nanosuspension treatment decreased TNF-α levels in wound tissue and accelerated the collagen deposition. Whereas, HSP-27, ERK, PDGF-B and VEGF expression increased and improved new blood vessels’ development. Rapid re-epithelization, fibroblast migration, collagen deposition and reduced inflammatory cell infiltration at the wound site were also observed.Conclusion: Results indicate that sesamol-PLGA nanosuspension significantly promotes the acceleration of wound healing in diabetic foot ulcers by restoring the altered wound healing process in diabetic condition.Keywords: diabetes, diabetic foot ulcer, sesamol, PLGA, nanosuspension, controlled release, wound healing, re-epithelization, angiogenesis, TNF-α